2014
DOI: 10.1016/j.visres.2014.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Temporal entrainment of visual attention in children: Effects of age and deafness

Abstract: The major documented effect of auditory deprivation on visual processing is enhanced spatial attention, in particular to the visual periphery and to moving stimuli. However, there is a parallel literature that has reported deficits in temporal aspects of visual processing in individuals with profound hearing losses. This study builds upon previous work showing possible deficits in processing of rapid serial visual presentation streams in deaf children [Restorative Neurology and Neuroscience (2010), 28, 181–192… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 33 publications
3
12
0
3
Order By: Relevance
“…6,20 Such access could be compromised by early deafness. 6,21 Application of a connectome model to individuals with sensory impairment suggests that outcomes of hearing loss and subsequent cochlear implantation will extend beyond the direct result of sensory loss—eg, perception of spoken language in the case of hearing. As a result, factors accounting for individual differences and variation in clinical outcomes after cochlear implantation will not be confined to the auditory system itself—they might range from effects at the cellular level to those at the social level and reveal themselves in complex cognitive functions.…”
Section: Application Of a Connectome Model To Neurosensory Restorationmentioning
confidence: 99%
See 1 more Smart Citation
“…6,20 Such access could be compromised by early deafness. 6,21 Application of a connectome model to individuals with sensory impairment suggests that outcomes of hearing loss and subsequent cochlear implantation will extend beyond the direct result of sensory loss—eg, perception of spoken language in the case of hearing. As a result, factors accounting for individual differences and variation in clinical outcomes after cochlear implantation will not be confined to the auditory system itself—they might range from effects at the cellular level to those at the social level and reveal themselves in complex cognitive functions.…”
Section: Application Of a Connectome Model To Neurosensory Restorationmentioning
confidence: 99%
“…67 Executive functioning consists of multiple components—ie, working memory, controlled attention, self-monitoring, organisation, inhibition, flexibility-shifting, and goal direction. 68 Verbal working memory, 69,70 controlled cognitive fluency, 67,71 re distribution of attentional resources, 21,72,73 and inhibition–concentration are at risk for delays in individuals with early deafness despite cochlear implantation. 66,74,75 Verbal working memory is assessed with neurocognitive methods that require individuals to hold a sequence of familiar verbal stimuli— eg, digits, letters, or words—in immediate memory while simultaneously engaging in another cognitive activity, such as reversing the order of test items or completing a simple mental calculation (appendix).…”
Section: Clinical Assessment Of Neurocognitive Outcomesmentioning
confidence: 99%
“…In particular, we ultimately aimed at testing to what extent sign language proficiency exerts an effect on overt visual selection performance in deaf adults that is specifically outside a linguistic context and without the presence of social stimuli, such as face-related stimuli. Recent evidence obtained with deaf children in a rapid serial visual presentation (RSVP) task does indeed suggest that the linguistic background of deaf participants may influence their performance on covert visual attention tasks (Dye, 2014; see also Dye & Bavelier, 2010). The linguistic assessment was carried-out in a separate and dedicated experimental session.…”
Section: Participantsmentioning
confidence: 99%
“…There is also strong evidence that recruitment of the sensory‐deprived auditory cortex underlies enhancement of the remaining sensory modalities (see Alencar, Butler, & Lomber, for a review). However, other results modulate this advantage and show that when temporal areas are involved in visual processing deaf children and adults, even those who have been exposed to natural sign language from birth perform less well (Dye, ). This is in accordance with Conway's hypothesis, which postulates that the absence of sound early in development results in disturbances to the development of general cognitive abilities related to representing temporal or sequential patterns (Conway, Pisoni, Anaya, Karpicke, & Henning, ; Conway, Pisoni, & Kronenberger, ).…”
Section: Introductionmentioning
confidence: 99%
“…Research has also shown that deaf participants have a visual advantage when stimuli are presented in the visual periphery (Codina et al, ; Megreya & Bindemann, ; Smittenaar, MacSweeney, Sereno, & Schwarzkopf, ). This advantage disappears when temporal components are involved (Dye, ). It can be assumed that sound is inherently a temporal and sequential signal: The coding of time seems to be more accurate for auditory events than for visual events (Glenberg & Jona, ).…”
Section: Introductionmentioning
confidence: 99%